Are Competitive Strategies and Strategic Alliances Role in Improving Sustainability Performance? - WERASTUTI, Desak Nyoman Sri; SUKOHARSONO, Eko Ganis; SARASWATI, Erwin; PRIHATININGTIAS, Yeney W. W. (Journal of Environmental Management and Tourism, 2019)
Performance measurement in the hospitality sector is not only demanded on financial performance but also expected in the non-financial sector so as to create environment and business goals that are environmentally friendly. Sustainable performance in the hotel sector is expected to provide awareness and demands that hotel managers pay more attention to environmental aspects so as to enhance the hotel's reputation for being environmentally friendly, comfortable with customers, can directly improve services to customers so as to create competitive strategies and strategic alliances for customers. This study aims to determine whether competitive strategies and strategic alliances can play a role in improving sustainable performance. This research was conducted in all 4 and 5-star hotels in Bali Province using questionnaires given to 154 respondents with 125 samples (questionnaire returns). The method used was Structural equation model (SEM). The results showed that the relationship of competitive strategies to sustainable performance had a positive and significant effect, the strategic alliance relationship to sustainable performance had a positive and significant influence as well as the strategic alliance relationship by mediating competitive strategies towards sustainable performance had a positive and significant effect.